Fish oil acidity reduction by enzymatic esterification. (October 2017) - Mata, Teresa M.; Correia, Daniela; Pinto, Ana; Andrade, Soraia; Trovisco, Isabel; Matos, Elisabete; Martins, António A.; Caetano, Nídia S.
Abstract: This work studies the enzymatic esterification for fish oil acidity reduction. Lipozyme TL 100L showed greater acidity reduction (75 %) for esterification at 40 °C, with ethanol 96 %, with enzyme/oil and alcohol/FFA mass ratios of respectively 0.01 and 3.24 w/w, reaching 3.13 mg KOH/g oil of final acid value or 1.57 % FFA content. Lipozyme CALB L showed greater acidity reduction (76 %) for esterification at 45 °C, with ethanol 99.8 %, with enzyme/oil and alcohol/ FFA mass ratios of respectively 0.0045 and 4.92 w/w, reaching 3.33 mg KOH/g oil of final acid value or 1.67 % FFA content.